Synthesis and Structural Characterization of Five-Coordinate Cobalt(II) Complexes Based on tris(2-Benzimidazolymethyl)amine Ligand - Ge, Chun-Hua; Li, Li-Hua; Wang, Ying-Qi; Zhang, Rui; Zhang, Xiang-Dong (Asian Journal of Chemistry, 2014)
The synthesis and characterization of three new complexes 2[Co(ntb)(H2mpda)]·(CH3COCH3)·4H2O (1), [Co(ntb)(H2mpda)]·3H2O (2) and 2[Co(ntb)Cl]·[Co(edta)]·6H2O (3) (ntb = N,N,N-tris(2-benzimidazolymethyl)amine, H4mpda = 1,3-phenylenedinitrilotetraacetic acid and H4edta = ethylenediamine tetraacetic acid) are reported. The molecular structures of these complexes are confirmed by single-crystal X-ray structure analysis. The reaction of Co(NO3)2 with ntb and H4mpda in acetone/H2O/ethanol or DMF/H2O/methanol gives 1 and 2, respectively, while the reaction of CoCl2 with ntb and H4edta in H2O/methanol gives 3. Mononuclear [Co(ntb)(L)] motif is found in all the compounds, in which Co(II) is in a five-coordinate environment with a tetradentate N4 coordination ntb ligand and a monodentate second ligand. The diversity of solvent in 1 and 2 results in slight difference in the coordinate and crystal packing structure. 3 is an ionic compound, containing [Co(ntb)Cl]+ cations and [Co(edta)]2- anions. The solvent plays significant role in the stabilization of all the three-dimensional supramolecular networks through hydrogen bonds.